Sources of sediments accumulating in the lower Black and Vygekraal Rivers, Cape Town, South Africa - Macdonald, Alexander James (Department of Environmental and Geographical Science, 2023)
Soil erosion within the catchment areas of the Black, Vygekraal and Elsieskraal Rivers (Cape Town, South Africa) results in sediment transport by these rivers, their tributaries, and the stormwater drainage systems which flow into these rivers. This sedimentary material is subsequently deposited in the lower reaches of the Black and Vygekraal Rivers owing to a decrease in the competence of the watercourse in this area. The resultant accumulation of sediment necessitates costly annual dredging of this section of river (referred to in this study as the "dredged area") by the Cape Town City Council. The loss of soil cover within the three catchments is initiated mainly by wind in summer, and by rain in winter. Soil erosion is likely to be of greatest magnitude in the Vygekraal catchment, owing to the extensive exposure of the natural sand cover as a result of poorly vegetated areas. Steep slopes, and construction works linked to urban development, also render the upper parts of the Elsieskraal catchment vulnerable to soil erosion. A relatively insignificant amount of soil loss is believed to occ~_r within the catchment of the Black River. Measurements and estimations of the relative transporting powers of the Black, Vygekraal and · Elsieskraal Rivers showed that the Vygekraal River was likely to have the greatest capacity to transport sediment throughout the year, while the Black River would have the least capacity. Particle size analyses of the watercourse sediments in the study area showed that the sands of the Cape Flats, i.e., within the Vygekraal catchment area, were the most easily transported sediments in the study area, by both water and wind. Finer alluvial sediments in the Tygerberg "Hills region (in the upper Elsieskraal catchment), directly derived from the loam soils of the area, were also found to be easily transported by natural elements. The coarser sediments in the Black River catchment were ·probably transported at a significantly slower rate, than were the fine sediments of the Elsieskraal River, and the medium-grained sands in the Vygekraal catchment area X-ray diffraction analysis of the clay component of the sediments indicated that the sediments accumulating in the extreme lower sector of the dredged area probably had their source in the upper Elsleskraal catchment area. Microscopic studies of the modal sand fractions of the sediments showed that it was likely that the sediments deposited in the upper and middle parts of the dredged area were almost exclusively derived from the catchment of the Vygekraal River, while the sediments in the lower part of the dredged area were equally likely to have originated from either of the three catchments. Multivariate statistical analyses were performed on the data set comprising the variables generated by the particle size analyses. The results from these investigations showed that, for the dredged area as a whole, the largest contribution of sediment came from the Vygekraal River, with the least from the Black River. The proportionate contribution of the Elsieskraal River to the total sediment accumulation in the dredged area · is likely, therefore, to be intermediate to those from the Vygekraal and Black Rivers. Further, more detailed studies of sediment transport and soil loss would be necessary in order to accurately determine the percentage contribution of each of the Vygekraal, Elsieskraal and Black Rivers to the total quantity of sediment accumulating annually in the dredged area.